A Multicenter Study of the Predictive Value of Crescents in IgA Nephropathy - Haas, Mark; Verhave, Jacobien C.; Liu, Zhi-Hong; Alpers, Charles E.; Barratt, Jonathan; Becker, Jan U.; Cattran, Daniel; Cook, H. Terence; Coppo, Rosanna; Feehally, John; Pani, Antonello; Perkowska-Ptasinska, Agnieszka; et al. (Journal of the American Society of Nephrology, 2017)
The Oxford Classification of IgA nephropathy does not account for glomerular crescents. However, studies that reported no independent predictive role of crescents on renal outcomes excluded individuals with severe renal insufficiency. In a large IgA nephropathy cohort pooled from four retrospective studies, we addressed crescents as a predictor of renal outcomes and determined whether the fraction of crescent-containing glomeruli associates with survival from either a ≥50% decline in eGFR or ESRD (combined event) adjusting for covariates used in the original Oxford study. The 3096 subjects studied had an initial mean±SD eGFR of 78±29 ml/min per 1.73 m 2 and median (interquartile range) proteinuria of 1.2 (0.7–2.3) g/d, and 36% of subjects had cellular or fibrocellular crescents. Overall, crescents predicted a higher risk of a combined event, although this remained significant only in patients not receiving immunosuppression. Having crescents in at least one sixth or one fourth of glomeruli associated with a hazard ratio (95% confidence interval) for a combined event of 1.63 (1.10 to 2.43) or 2.29 (1.35 to 3.91), respectively, in all individuals. Furthermore, having crescents in at least one fourth of glomeruli independently associated with a combined event in patients receiving and not receiving immunosuppression. We propose adding the following crescent scores to the Oxford Classification: C0 (no crescents); C1 (crescents in less than one fourth of glomeruli), identifying patients at increased risk of poor outcome without immunosuppression; and C2 (crescents in over one fourth of glomeruli), identifying patients at even greater risk of progression, even with immunosuppression.